2010
DOI: 10.1093/icb/icq028
|View full text |Cite
|
Sign up to set email alerts
|

Local Temperature Fine-Tunes the Timing of Spring Migration in Birds

Abstract: Evidence for climate-driven phenological changes is rapidly increasing at all trophic levels. Our current poor knowledge of the detailed control of bird migration from the level of genes and hormonal control to direct physiological and behavioral responses hampers our ability to understand and predict consequences of climatic change for migratory birds. In order to better understand migration phenology and adaptation in environmental changes, we here assess the scale at which weather affects timing of spring m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
96
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 40 publications
7
96
1
Order By: Relevance
“…The bulk of currently available ringing data is often derived from long-term projects carried out at permanent ringing stations where large amount of individuals of various species are trapped simultaneously . These projects generally apply standardized methodologies in trapping, handling and data collection, thus information derived from these sites is suitable for location-wise comparisons (Schaub & Jenni 2000, Marra et al 2004, Schaub et al 2008, Tøttrup et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The bulk of currently available ringing data is often derived from long-term projects carried out at permanent ringing stations where large amount of individuals of various species are trapped simultaneously . These projects generally apply standardized methodologies in trapping, handling and data collection, thus information derived from these sites is suitable for location-wise comparisons (Schaub & Jenni 2000, Marra et al 2004, Schaub et al 2008, Tøttrup et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Although long-distance migrants seem to be under endogenous control for the onset of spring migration [16], our study highlights that many of the species that were significantly affected by temperature changes and those that have altered their migration timing through the state of New York were long-distance migrants (Tables 1-4). Tøttrup et al [13] concluded that local spring temperatures in migratory route are the best predictors of bird phenology, despite whether the migrating specie is a short-or long-distance migrant. Similar patterns of shift in migratory strategy for long-distance migrants have been documented for birds on Helgoland [33] and birds in Scandinavia and southern Italy [12].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, timing of migration is said to be adjustable prior to departure when physiologically challenging environmental conditions pose additional threats to the bird, or it can be altered mid-migration when improved environmental conditions at stopover sites can reduce the time required to refuel [13]. However, timing of migration can be further complicated by effects of climate change, weather en route, and population declines, as well as the rate at which birds can refuel during stopover [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The bulk of currently available data is often collected at permanent, long-term ringing stations where large amount of individuals of various species are trapped simultaneously . These projects generally apply standardized methodologies in trapping, handling and data collection, thus information derived from these sites is suitable for location-wise comparisons (Schaub & Jenni 2000, Marra et al 2004, Schaub et al 2008, Tøttrup et al 2010.…”
Section: Introductionmentioning
confidence: 99%